Beginning Lua programming - Jung, Kurt, 1956- (Wrox beginning guides., 2007)
Lua offers a wide range of features that you can use to support and enhance your applications. With this book as your guide, you'll gain a thorough understanding of all aspects of programming with this powerful language. The authors present the fundamentals of programming, explain standard Lua functions, and explain how to take advantage of free Lua community resources. Complete code samples are integrated throughout the chapters to clearly demonstrate how to apply the information so that you can quickly write your own programs.